Bullying di Sekolah dan Dampaknya bagi Masa Depan Anak - Ahmad Baliyo Eko Prasetyo (Islamic University of Indonesia, 2011)
This paper aims at reviewing bullying at schools, including its definitions, characteristics, forms and factors preceding it. More specifically, this paper discusses the effects of bullying on children’s future. According to literatures and some various researches, bullying in childhood and in school days allegedly becomes one of main factors that caused psychological disorders in their adulthood. Some of recorded disorders that are related to long-term impact of bullying at school days are Post-Traumatic Stress Disorder (PTSD), depression, lack of confidence, and withdrawal. Eventually, this paper will propose the ways and methods in solving and preventing bullying and its impacts.